Eficácia dos soros antiofídicos de uso veterinário na neutralização das atividades biológicas dos venenos de Bothrops atrox (Linnaeus, 1758) e Crotalus durissus ruruima (Hoge, 1965) - Noronha, Maria das Dores Nogueira (2008)
Human snake bite accidents by Bothrops atrox (in Amazonian Region) and Crotalus durissus ruruima (in Roraima State) are frequently and antivenom serological therapy is the better treatment. Today, exist in the market veterinary antibotropic-anticrotalic, antivenenos liquid and liophylized presentation. Snakes shown molecular and biological activities variations in yours venoms, including in specimens from same specie. To clinical use, veterinary antivenoms neutralizing efficacy against venoms from regional species are necessary be tested. We are introducing in this work the neutralizing efficacy of veterinary antiophydian antivenom against biological activities from B. atrox and C. d. ruruima venoms. Also human antibotropic and anticrotalic antivenins with clinical use expired date were tested. 2D electrophoreses Molecular profile from B. atrox venom shown 23 and 50 kDa haemorrhagic metalloproteinases toxins as principal constituents. Molecular profiles from C. d. ruruia “White”and ÿellow” venoms suggest that 50 kDa toxins and 14 kDa basic toxins have a differencial expression of your genes in sample specimens venom glands. Veterinary liquid antivenom neutralizing efficacy os hemorrhagic PLA2 coagulant and desfibrinogen activities from venoms studiet was better that veterinary liophylized antivenom. Anticrotalic antivenom not neutralized hemorrhagic activity from C. d. ruruima venom. Western blotting test showed antigen-antibody interactions with all antivenoms used, but veterinary liquid antivenom showed more neutralizing potency that veterinary liophylized antivenom against lethal activity from B. atrox venom. Neutralizing potency against lethal activity from C. d. ruruima venom was very low in both veterinary antivenoms. Human antivenoms showed high neutralizing potency against lethal activity from venoms studied. Clinical datas are necessary to known real neutralizing efficacy from veterinary antiophidian antivenoms against biological activities from Amazonian snake venoms. Key-words: Bothrops, Crotalus, veterinary antiophydian antivenom.